Exploración de las potencialidades del relato de corta duración en la serie web "Romances de 20 centavos" - Pareja Mendiola, Ana Paula (2020)
This document explains carefully the creation and development of the web series project “Romances de 20 centavos”, formulated as an exploration of the possibilities of the short- term storytelling in the digital format given a context where the web series current offer is usually based in narrative models that simulate the narrative mechanism of series with longer durations. That is why this project aspires to generate less explored formulas base on narrative resources that are more effective in a short story as the dosification of the information and the use of suspense and surprise.